International Business Opportunities and Reasons Why Major Canadian Banks Should Offer Islamic Finance - Al-Dimashki, Obada (Global journal of Business and Integral Security, 2024)
The global financial landscape has witnessed a remarkable surge in interest and adoption of Islamic finance products, reflecting a significant growing demand for Shariah-compliant banking solutions. This research delves into the opportunities and underlying reasons that advocate for major Canadian banks to incorporate Islamic finance products into their offerings. Canada’s multicultural and diverse population, including a substantial Muslim demographic, presents a unique opportunity for major banks to tap into an underserved market segment. The incorporation of Islamic finance products could cater to the financial needs of Muslim consumers, fostering inclusivity and aligning with the country’s commitment to human rights, diversity, and social harmony. Furthermore, the global nature of Islamic finance provides Canadian banks with the prospect of expanding their reach beyond national borders. By introducing Shariah-compliant products, these banks could establish a foothold in international markets that have embraced Islamic finance principles, expand capital raising capabilities, enhance global competitiveness and strengthen their brand image. Challenges such as regulatory considerations and operational adjustments are also discussed within the context of this research. By addressing these challenges through strategic planning, collaboration, tailored marketing and advising, major Canadian banks can pave the way for the successful integration of Islamic finance products.